Unjuk Kerja Organic Rankine Cycle Dengan Penyerap Energi Matahari Type Concave Plate Collector Pada Temperatur Sumber Panas 75 Oc - Arifful Rahman; Awaludin Martin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
This study discusses the experimental study of the efficiency of the Organic Rankine Cycle (ORC) system with concave plate collectors as a heat source system. ORC is a conventional rankine cycle modification, where the ORC fluid works is an refrigerant or organic fluid which has a low boiling point, so that to produce steam only requires a low temperature. A good working fluid is R134a obtained from the reference of previous studies. Concave plate collector is heat source system at electricity generation system that is concentrated using the sun as a source of heat, so it can be said that this system uses environmentally friendly renewable energy sources. Experiments were carried out by varying the heat source temperature of 75 ⁰C by keeping the pump output pressure at 10 bar and comparing the test results between the use of a water heater and a combined water heater with a concave plate collector. From the experimental results obtained a maximum efficiency of 0.7% on the variation of heat source 75 ⁰C with a turbine inlet pressure of 10.1 bar and turbine intake temperature of 46.9 ⁰C with ORC power of 170.4 Watt. The biggest savings or energy supply for solar collectors is 68.33% at solar collector temperatures of 56.8 ° C with average temperature of heat sources of 70.38 ° C.Keyword : Organic Rankine Cycle, R134a, Solar collector, Renewable Energy.